Structural analysis of the common ragweed (Ambrosia artemisiifolia L.) chloroplast genome - Nagy , Erzsébet; Taller, János (GEORGIKON FOR AGRICULTURE, 2020)
Chloroplast is an essential organelle in plants. Besides its key role in photosynthesis fatty acids and many amino acids are synthesized in chloroplasts. Due to the endosymbiotic origin chloroplasts have their own DNA, the cpDNA that called also plastome. The chloroplast genome has well defined structure and due to its conservative nature slow evolution is characteristic for it. In the present study we analyzed the plastome structure of common ragweed (Ambrosia artemisiifolia), the most widespread and highly allergenic weed in many parts in the world. Compared to other chloroplast genomes, the analysis indicates the differences in start codon of some genes, in gene content and structure, in intron content, as well as the repeated sequence motifs are identified, with special attention on the potential microsatellites. Results of this study can be utilized in future phylogenetic analyses and genotyping.
Keywords: common ragweed; chloroplast genome; plastome genes; repeats; microsatellites